Trading de moneda electrónica mediante la plataforma Binance en Colombia (2021)
In this document the reader will find the analysis related to the analysis of electronic currency trading through the Binance platform in Colombia. For the purposes of developing this document, objectives were formulated and chapters were raised in which each of the elements comprising the research development was systematically described as: trading in electronic currency, The dynamics of the electronic currency, investment in the stock exchange of the electronic currency and the presentation of a real case of the financial year in the platform Binance, to close this document conclusions were raised and the bibliography of research support was presented.